Cluster as a Form of Strategic Alliance - Marzena Godlewska; Elżbieta Weiss (Contemporary Economics)
The article presents the theory of clusters that are treated as natural elements of European model of economic development. There are highlighted Polish Forum of Lisbon Strategy point of view that indicated clusters as one of fundamental ideas recommended for Polish economy. In based on literature and observation of articleís authors the concept, examples of Polish clusters and their role in strategic alliance are presented.